PERKAWINAN BEDA AGAMA DAN KEBEBASAN INDIVIDUAL MANUSIA DALAM ISLAM: Perspektif â€œTeori Naskhâ€ Mahmoud Muhammad Thaha - Mustafid, Fuad (Musawa Jurnal Studi Gender dan Islam, 2011)
This article is part of an effort to empower families with respect to the issue of interreligious marriage. Until this time, Indonesia still adopts a legal system of internal religious marriage. Therefore, interreligious marriage has not been accommodated in Indonesia, in spite of widespread practice. This is becauseÂ  Islamic ulama(s) do not condone such marriages; as marriages are only seen to be valid if done within the same religion, a view adopted by the majority of Muslims. However, there are other views that allow for interreligious marriage. The reason being, that the prohibition of the Quran has temporal and conditional aspects, and that the application itself is not substantive in nature.Â  Therefore, the verse that prohibits such marriages arenaskh-ed (abrogated) by another allowing it. This allowance is in line with the freedom exercised by humans in religion. If humans have the freedom of religion, then they are also free to choose their life partners, and so goes the argument constructed by Mahmoud Mohammad Thaha, the philosopher from Sudan.